2017
DOI: 10.1038/emi.2017.26
|View full text |Cite
|
Sign up to set email alerts
|

A novel preventive strategy against HIV-1 infection: combinatorial use of inhibitors targeting the nucleocapsid and fusion proteins

Abstract: The strategy of simultaneously attacking multiple targets is worthy of exploration in the field of microbicide development to combat HIV-1 sequence diversity and minimize the transmission of resistant variants. A combination of S-acyl-2-mercaptobenzamide thioester-10 (SAMT10), an inhibitor of the HIV-1 nucleocapsid protein (NCp7), and the fusion inhibitor sifuvirtide (SFT) may exert synergistic effects, since SFT can block viral fusion at an early stage of the viral cycle and SAMT10 can disrupt viral particles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…HIV sequence data from freely available databases might be an important source for studies on HIV-1 diversity, which, in turn, might lead to new insights in novel drug discovery. In particular, an idea that inhibitors have to be developed to target conserved regions of different viral proteins is reflected in studies dedicated to HIV proteins diversity evaluation [ 6 , 81 , 82 , 83 , 84 ]. For instance, in the study of Li, G. et al, over 12,000 gag sequences from LANL database were analyzed in order to determine the relationship between a number of conserved positions in HIV-1 sequences and the probability of target to be promising for new potential antiretroviral drug discovery [ 80 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…HIV sequence data from freely available databases might be an important source for studies on HIV-1 diversity, which, in turn, might lead to new insights in novel drug discovery. In particular, an idea that inhibitors have to be developed to target conserved regions of different viral proteins is reflected in studies dedicated to HIV proteins diversity evaluation [ 6 , 81 , 82 , 83 , 84 ]. For instance, in the study of Li, G. et al, over 12,000 gag sequences from LANL database were analyzed in order to determine the relationship between a number of conserved positions in HIV-1 sequences and the probability of target to be promising for new potential antiretroviral drug discovery [ 80 ].…”
Section: Resultsmentioning
confidence: 99%
“…In particular, authors propose that the low values of intra-subtype diversity of gag capsid protein provide the support for considering it as a drug target. We should emphasize that currently the strategies of novel promising targets identification is in close neighborhood with the idea to combat multiple HIV targets simultaneously as well as new druggable targets search [ 10 , 83 ]. Probably in the near future new approaches and tools have to be developed to estimate the HIV targets, containing optimal density of conserved regions, which either can be attacked by an inhibitor or undergo potentially lethal mutations.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the nonspecific reactivity of 1 with cysteine thiols, it is remarkable that 1 can selectively interfere with HIV Gag processing and maturation without simultaneously interfering with other critical cellular functions. In this study and many previous experiments, cellular toxicity of 1 (as well as animal toxicity) is not observed at any concentration tested (TC 50 > 100 ÎŒM is typical for most cells, and in rats, the maximum tolerated dose is above 2 g per kg for a prodrug analogue of 1 when administered orally). ,− The reactivity of 1 indicates that there would be multiple acetylations of cysteines in non-HIV proteins, and indeed, we previously showed that 1 can react with other zinc-finger proteins in vitro . Consistent with this broad reactivity, the results in this study demonstrate that several cysteines in the MA and CA domains of Gag are acetylated by 1 along with a number of lysines in these domains.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this broad reactivity, the results in this study demonstrate that several cysteines in the MA and CA domains of Gag are acetylated by 1 along with a number of lysines in these domains. Although it is likely that 1 reacts similarly with other cellular proteins, the lack of toxicity in cells or animals treated with 1 and related molecules ,− indicates that any erroneous acetylations of cellular proteins either occur on a minor population of a given protein or are easily corrected within cells by existing enzymes, such as deacetylases. It is also likely that the intracellular levels of 1 are very low under homeostatic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Zinc ejectors showed potent antiviral activity and have been recently progressed through preclinical studies, even though most of the chemical agents from this class appeared to be quite toxic. Thus, their use as systemic antiretroviral agents has been discontinued in favor of their possible development as topical microbicides . Noncovalent NCIs targeting nucleic acids are generally low specificity DNA- or RNA-intercalating agents that mainly proved to be valuable tools in understanding NC functions and druggability.…”
mentioning
confidence: 99%